Associations between markers of social functioning and depression and quality of life in survivors of head and neck cancer: Findings from the Head and Neck Cancer 5000 study. Issue 3 (30th September 2021) - Patterson, Joanne M.; Lu, Liya; Watson, Laura‐Jayne; Harding, Sam; Ness, Andy R.; Thomas, Steve; Waylen, Andrea; Pring, Miranda; Waterboer, Tim; Sharp, Linda
Abstract: Objective: To investigate associations between markers of social functioning (trouble with social eating and social contact), depression and health‐related quality of life (QOL) among head and neck cancer survivors. Methods: This cross‐sectional analysis included individuals with oral cavity, oropharynx, larynx, salivary gland and thyroid cancers from Head and Neck 5000 alive at 12 months. Trouble with social eating and social contact were measured using items from EORTC QLQ‐H&N35 and QOL using EORTC QLQ‐C30; responses were converted into a score of 0–100, with a higher score equalling more trouble or better QOL. A HADS subscale score of ≥8 was considered significant depression. Associations between tertiles of trouble with social eating and social contact and depression and QoL were assessed using multivariable logistic and linear regression (with robust errors), respectively. Results: Of 2561 survivors, 23% reported significant depression. The median QOL score was 75.0 (interquartile range 58.3–83.3). For trouble with social eating, after confounder adjustment, those in the intermediate and highest tertiles had higher odds of depression (intermediate: OR = 4.5, 95% CI 3.19–6.45; high: OR = 21.8, 15.17–31.18) and lower QOL (intermediate: β  = −8.7, 95% CI −10.35 to −7.14; high: β  = −24.8, −26.91 to −22.77). Results were similar for trouble with social contact. Conclusion: We found strong clinically important associations between markers of social functioning and depression and QOL. More effective interventions addressing social eating and contact are required. These may help survivors regain their independence, reduce levels of isolation and loneliness, and depression, and improve QOL outcomes generally.